Asiatic Acid Prevents Oxidative Stress and Apoptosis by Inhibiting the Translocation of α-Synuclein Into Mitochondria - Ding, Hongqun; Xiong, Yuyun; Sun, Jing; Chen, Chen; Gao, Jing; Xu, Huaxi (Frontiers in Neuroscience, 2018)
The association of α-synuclein (α-syn) with mitochondria occurs through interaction with mitochondrial complex I. Defects in this protein have been linked to the pathogenesis of Parkinson disease (PD). Overexpression of α-synuclein in cells has been suggested to cause elevations in mitochondrial oxidant radicals and structural and functional abnormalities in mitochondria. Asiatic acid (AA), a triterpenoid, is an antioxidant that is used for depression, and we have shown that pretreatment with AA can prevent PD-like damage, but its therapeutic effects in PD and mechanism remain unknown. In this study, we found that 0.5–2 mg AA/100 g diet significantly improves climbing ability in drosophila and extends their life-span—effects that we attributed to its antioxidant properties. AA also protected mitochondria against oxidative stress and apoptosis in a rotenone-induced cellular model. In an isolated mitochondria model, AA attenuated the decline in mitochondrial membrane potential that was induced by α-syn. Consequently, AA maintained membrane integrity and ATP production. Finally, we demonstrated that AA protects by blocking the translocation of α-syn into mitochondria. Our results suggest that mitochondria are crucial in PD and that AA is an excellent candidate for the prevention and therapy of this disease.